The experience of loneliness in adolescence - O. Ljovochkina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article is analysis of approaches to experience loneliness. This article determined basic definition of "loneliness", which is considered as a mental condition, which reflects the experience of their separateness, subjective inability or unwillingness to feel adequate review, acceptance and recognition of his others. This article also analysis the problem of adolescent loneliness. It is noted that the feeling of loneliness adolescents often leads to negative consequences. However, adolescent loneliness can take both positive and negative. Negative emotions cause you to lose self- esteem, self- sympathy, if the experience is positive – adolescents have an interest in self. In turn, the interest in self can encourage adolescents to activities that promote personal growth, resulting in: a person becomes more open to experience less psychological defence uses more realistic and objective more effectively solve their problems; improved psychological adaptability and reduced vulnerability; perception of his "I" – is close to the ideal "I" – the real; decreases anxiety, and physiological and mental stress; increased self-esteem; individual becomes more realistic and more adequately perceive others and are perceived by others behaviour of the individual as a socially responsible; behaviour is more adaptive and creative. U this regard, the task of the psychologist should identify adolescents characterized by high levels of negative feelings of loneliness; help them realize their own limitations and psychological change negative to positive feelings of loneliness, awakening in him an interest in self and finding ways of personal growth; using certain psychological technology to help teenagers steer processes that accompany the feeling of loneli- ness, to achieve personal growth and positive changes in their lives. It is proposed to conduct a psycho teenagers and developmental activities aimed at overcoming the adverse conditions associated with a sense of loneliness, as well as the use of state of loneliness to self-knowledge and personal growth of adolescents.
Keywords: loneliness as a psychological phenomenon; experience loneliness; adolescent loneliness; personal growth